Research on the energy efficiency of the anaerobic fermentation process of animal waste - Chmil, A. (Energy and Automation, 2025)
Analysis of the problem of energy supply of agricultural production shows that the existing difficulties in the field are caused by human violation of the biological law of bioenergetic orientation of living systems, according to which all components of living nature are energy-saving. At the same time, the effect that has been provided so far by using a certain amount of energy carriers can be obtained with a smaller amount of them, if additional measures are taken to save energy and use non-traditional energy sources. Due to the depletion of fossil fuel reserves and the constant deepening of the energy and environmental crisis, considerable attention is paid to renewable and non-traditional energy sources. However, despite the fact that this energy itself is free, the equipment necessary for utilization and conversion is quite expensive. The main advantage of renewable and non-traditional types of energy is the inexhaustibility of the latter. The fact that farm animals poorly absorb the energy of plant feeds, and that more than half of this energy is used unproductively, allows us to consider manure and droppings not only as a valuable raw material for organic fertilizers and a protein supplement to animal feed, but also as a powerful renewable source of energy in agricultural production. As a heat and energy raw material, animal manure can be used to produce combustible gas, which consists of 2/3 of methane - one of the most valuable and high-calorie types of fuel. And although modern technological schemes for biogas production are still inferior to traditional natural sources in terms of economic indicators, a significant number of biogas plants are operating in most foreign countries, which provide up to 20-40% of energy needs in agriculture. An effective way to utilize livestock manure is anaerobic fermentation in biogas plants. During fermentation, animal excrement is largely disinfected, pathogenic microflora dies, weed seeds lose their germination, and in addition, biogas is released, the utilization of which allows obtaining additional energy. This way of manure utilization under the conditions of gradual depletion and increase in the cost of traditional sources is gaining special importance. Since fermentation is carried out in closed structures, completely isolated from the environment, the possibility of the spread of infections and gases with an unpleasant odor and the ingress of untreated manure into the soil, ground and groundwater is eliminated. As a result of the decomposition of organic substances in the fermented product, the proportion of biogenic elements increases, most of them are converted into easily digestible mineral substances by plants, and nitrogen losses do not exceed 3-5%. An experimental installation was developed to determine the nature of gas evolution, the depth of mineralization of organic matter depending on the regime and design parameters, as well as to develop technological schemes for anaerobic treatment and utilization of waste from livestock enterprises based on the obtained dependencies. Key words: organic waste, anaerobic fermentation, energy efficiency livestock waste, anaerobic fermentation, energy efficiency